REACTION OF GREEN LEAF LETTUCE GENOTYPES TO THREE SPECIES OF ROOT-KNOT NEMATODES ACCORDING TO TWO EVALUATION METHODS - Diniz, G. M. M. [UNESP]; Candido, W. S. [UNESP]; Rabelo, H. O. [UNESP]; Marin, M. [UNESP]; Braz, L. T. [UNESP]; Soares, P. L. M. [UNESP] (Organization Trop Amer Nematologists, 2018)
This experiment employed two evaluation methods to determine the reaction of green-leaf lettuce genotypes to Meloidogyne enterolobii, M. javanica, and M incognita. Two hundred second-stage juveniles (J2) of each nematode species were separately inoculated on eight green leaf lettuce inbred lines developed by UNESP/FCAV. The cultivar 'Vanda' was also evaluated, as well as tomato cultivar 'Santa Cruz Kada' to aid in detecting a pattern of susceptibility. The host-plant reactions to the nematodes were determined by the root gall index (GI), egg mass index (EMI) and reproduction factor (RF). Treatments were arranged in a completely randomized design, in factorial 3 x 9 with seven replications. The results changed according to the method. The inbred line L, was moderately resistant to all the nematodes based on GI. However, all the genotypes were considered susceptible to root-knot nematodes considering RF reaction.
Keywords: gall index; Lactuca sativa L.; Meloidogyne spp.; reproduction factor; resistance